A new role of SGLT-2 - treatment of IgA-nephropathy? - Syeda Zeenat Sahar Junaid; Muhammad Muntazir Mehdi Khan; Henna Fatma (Journal of the Pakistan Medical Association, 2022)
Sodium Glucose co-transporter 2 inhibitors (SGLT2) paved their way into traditional science books less than a decade ago as a new class of drugs treating diabetes. However, the ongoing discovery of their ever-widening array of uses shows that we are still yet to tap into their full potential. SGLT2 inhibitors or the “gliflozins” selectively target SGLT2 co-transporters in proximal tubules of the nephron. The inhibition reduces the renal threshold for glucose reabsorption, resulting in glucosuria and lowering blood glucose levels. They have added benefits in kidney and cardiovascular outcomes in diabetics. These positive reno-protective effects are not just exclusively for diabetic patients- non-diabetic chronic kidney disease (CKD) may benefit from gliflozins. Ig-A nephropathy (IGAN) is the most common glomerulonephritis worldwide. There is no population-based prevalence in Pakistan, but various centres have reported a prevalence between 2-20.83%(1).A multitude of drug candidates have been investigated to halt disease progression, including RAAS inhibitors, steroids and immunosuppressants, but have not shown significant utility. —Continue